Medieval Slavic Translations of the "Miracles of Saint Menas": Sources and Textual Problems - Stradomski, Jan (Vox Patrum, 2025)
A collection of miracles attributed to St Menas appeared in medieval Old Church Slavonic literature as a result of contacts between Orthodox Slavs in the Balkans and Byzantine Christian literature. By the 10th century, at least two distinct translations of the had likely been produced in Bulgaria. These translations have been preserved in Slavic collection manuscripts (dating from the late 13th to the 17th centuries) in both an abridged version (a compilation of several miracles) and a full translation of the entire collection, comprising 13 miracles. This article presents the current state of research on the subject, the most important sources, the hypothesized routes of migration of Greek sources into Old Church Slavonic (and later Church Slavonic) literature, and a proposed reconstruction of the transmission process of these translations within the Slavic textual tradition.